Synthesis, Anti-inflammatory and Molecular Docking Study of Schiff Bases Containing Methanesulphonyl Pharmacophore - R. A. Abdellatif, Khaled; T. Elsaady, Mohammed; A. Abdel-Aziz, Salah; H. A. Abu Sabah, Ahmed (Letters in Drug Design & Discovery, 2017)
Background: A series of 5-(arylideneamino)-1H-pyrazole-4-carbonitriles 8a-h was synthesized via reaction of triethylorthoformate 1 with malononitrile 2 in presence of acetic anhydride to give ethoxymethylenemalononitrile 3. Compound 3 was reacted with 4-methanesulfonylphenylhydrazine 4 to give 5-amino-1H-pyrazole-4-carbonitrile 5 that condensed with different aromatic aldehydes 6a-h in presence of the ionic liquid morpholinium hydrogen sulphate 7 to form the target 5-(arylideneamino)-1H-pyrazole-4-carbonitrile compounds 8a-h. Methods: All the synthesized compounds were evaluated for their cyclooxygenase selectivity, antiinflammatory, and molecular docking study for COX 2 enzyme. 8a and 8e were the most potent COX-2 inhibitors (IC50 = 0.98, 1.3 μM respectively). Results: While most compounds showed good anti-inflammatory activity at all time intervals (1, 3 and 5 h), 8d derivative displayed the highest anti-inflammatory activities (94.61, 98.35, and 99.92%, respectively) and the most COX-2 selective derivatives 8a and 8e showed considerable potency (47.43, 88.94, and 98.44% respectively for 8a and 51.90, 89.13, and 98.20% respectively for 8e) comparable to that of celecoxib (92.77, 97.77, and 99.51% respectively). Also, 8d showed less ulceration effect (ulcer index = 2.9) than celecoxib (ulcer index = 3.35) and aspirin (ulcer index 22.75). Conclusion: Additionally, all the tested compounds showed good binding affinity for COX 2 enzyme in the molecular docking studies.
Keywords: Arylideneamino-1H-pyrazole